GEOTECHNICAL ASSESSMENT OF SUBLAKE SLOPES AND LIQUEFACTION HAZARD IN LAKE TOBA, INDONESIA - Ariani, Listia; Faris, Fikri; Rifa'i, Ahmad (GEOMATE Journal, 2023)
Lake Toba, the largest lake in Sumatra Island, is a volcanic lake that holds great significance both geologically and culturally. It has a breathtaking natural wonder that captivates visitors from around the world. The fluctuation of surface levels in Lake Toba adds another layer of complexity to the stability of its sublake slopes during seismic activity. The key aim of this paper is to study the sublake slope stability, likelihood of liquefaction potential, and permanent deformation that subject to the fluctuation of Lake Toba surface levels. This research was conducted the numerical analysis of GeoStudio 2022.1 software by combining QUAKE/W, SLOPE/W, and SIGMA/W to evaluate the pre- and post-earthquake condition. The slope stability in the pre-earthquake condition was stable regardless of the reduced safety factor along with the declining lake surface level, but in the post-earthquake condition the safety factor was reduced nearly 60%, resulting in slope instability. An earthquake exhibits 0.25 g of acceleration within a period of 44.435 s, caused liquefaction up to 7.7 m layer of soil structure and high amplification of the ground surface approximately to 0.44 g. Massive permanent deformation occurred as the result were varying from 7 m to 12.1 m. As the surface level decreases, potential for liquefaction decreases as well but the safety factor value of slope stability increases, which can lead to a greater increase in the potential for permanent deformation. This indicates that the declining of the lake surface level influences slope failure during an earthquake.